Sleep disorders and late-onset epilepsy of unknown origin: Understanding new trajectories to brain amyloidopathy. (March 2021) - Liguori, Claudio; Spanetta, Matteo; Romoli, Michele; Placidi, Fabio; Nardi Cesarini, Elena; Mercuri, Nicola Biagio; Costa, Cinzia
Highlights: Sleep disorders have been associated with increased risk of developing Alzheimer's Disease. Late-onset unexplained epilepsy is associated with Aß pathology. Aß pathology can be concurrently linked to sleep impairment and late-onset epilepsy. Abstract: The intertwining between epilepsy, sleep disorders and beta amyloid pathology has been progressively highlighted, as early identification and stratification of patients at high risk of cognitive decline is the need of the hour. Modification of the sleep-wake activity, such as sleep impairment or excessive daytime sleepiness, can critically affect cerebral beta amyloid levels. Both mice models and human studies have demonstrated a substantial increase in the burden of beta amyloid pathology after sleep-deprivation, with potential negative effects partially restored by sleep recovery. The accumulation of beta amyloid has been shown to be an early event in the course of Alzheimer's disease dementia. Beta amyloid accumulation has been linked to epileptic seizures epileptic seizures, with beta amyloid being itself pro-epileptogenic in mice models already at oligomeric stage, well before plaque deposition. Further supporting a potential relationship between beta amyloid and epilepsy: i) seizures happen in 1 out of oofut 10 patients with Alzheimer's disease in the prodromal stage, ii) epileptic activity accelerates cognitive decline in Alzheimer's disease, iii) people with late-onset epilepsy present a critically high risk of developing dementia. In this Review we highlight the role of beta amyloid as a potential shared mechanisms between sleep disorders, late-onset epilepsy, and cognitive decline.